Evaluation of Effectiveness of Fixed‐Station Sampling for Monitoring American Lobster Settlement. (21st September 2015) - Li, Bai; Cao, Jie; Chang, Jui‐Han; Wilson, Carl; Chen, Yong
Abstract: The American lobster Homarus americanus supports one of the most valuable fisheries in the USA. One of the important monitoring programs is for benthically settled lobsters, which closely relates to recruitment. The lobster settlement sampling program follows a fixed‐station design. However, the performance of this design has not been evaluated, and we are unclear if the design can capture the temporal dynamics of settlers, in particular in response to changes in spatial distribution of lobster in the last 2 decades. In this study, we compared the fixed‐station design with a random sampling design for the mid‐coast region of the Gulf of Maine. We developed a generalized additive model (GAM) to quantify the relationship between habitat variables and density of early benthic phase and older juvenile lobsters by using the data from inshore trawl surveys from 1989 to 2012. The GAM model was then used to simulate putative true populations using the habitat variables. The two different sampling designs were applied to sample the simulated true populations. The fixed‐station sampling design tended to underestimate the true density but could capture the temporal trends in settler density. A persistence index analysis suggests that the fixed‐station design could identify interannual change of the lobster settler density. This study suggests that fixed‐station sampling design is effective in monitoring temporal changes in settler density but could not be used for the estimation of absolute density of settlers. Received December 16, 2014; accepted July 9, 2015